A highly versatile fluorenone-based macrocycle for the sensitive detection of polycyclic aromatic hydrocarbons and fluoride anions. Issue 45 (30th May 2017) - Tamgho, Ingrid-Suzy; Chaudhuri, Sauradip; Verderame, Molly; DiScenza, Dana J.; Levine, Mindy
Abstract : Reported herein is the high yielding synthesis of a new fluorenone-based triazolophane and its sensing capabilities for polycyclic aromatic hydrocarbons (PAHs) and fluoride anions. Abstract : Reported herein is the high yielding synthesis of a new fluorenone-based triazolophane and its sensing capabilities for polycyclic aromatic hydrocarbons (PAHs) and fluoride anions. Fluorescence, UV/Vis and 1 H NMR spectroscopy results showed the triazolophane has a high sensitivity for selected PAHs and binds the fluoride anion in a 2 : 1 stoichiometry via C–H hydrogen bonding with the triazole and fluorenone protons.